Analysis of The Influence and Priority of Employer Branding Dimensions in Attracting Generation Z Job Applicants - Honanta, Cindy; Sitepu, Rismawati; Nainggolan , Romauli (Journal Research of Social Science, Economics, and Management, 2025)
Employer branding is a strategy for attracting and retaining potential employees amidst increasingly fierce competition. This strategy is particularly relevant for Generation Z employees, a young generation with unique characteristics and high expectations for a flexible, meaningful, and innovative work environment. When choosing a job, they consider not only financial aspects but also company values, opportunities for personal development, and work-life balance. Therefore, developing employer branding that meets the needs and expectations of Generation Z employees is key to companies remaining competitive and attracting quality talent. This study analyses the influence and priorities of four dimensions of employer branding: economic value (salary and compensation), social value (work environment and culture), development value (learning and career opportunities), and interest value (innovation and challenges). The methods used were multiple linear regression and the Analytical Hierarchy Process (AHP), involving 200 respondents, consisting of final-year undergraduate students and fresh graduates majoring in Information Technology, Engineering, and Management in Indonesia. The results of the study indicate that interest value is the strongest and most prioritized factor in attracting prospective Generation Z employees to apply for jobs, followed by economic value, which also has a significant influence. Development value was not proven to be significant, while social value tended to have a negative influence. These findings provide practical recommendations for companies to develop effective employer branding strategies,